Model Keseimbangan Kerjaya dan Rumah Tangga dalam kalangan Wanita Cemerlang Sektor Awam (Sains Humanika, 2015)
Being balance in managing household is a mandatory claim for working women. The diversity of techniques fulfil the trust and responsibility of the dual career. Therefore, the effective model according to Islamic views is much needed nowadays. Data were collected through qualitative design using in-depth interviews and analysis of documents involving past literatures and views of the contemporary scholars. In-depth interviews were conducted with women who excel in management and public sector and professionals with JUSA and grade 54. Supporting data of this study involved interviews with husbands, children, employers and colleagues to create a triangulation data. The findings of the study was analysed thematically using Nvivo 7.0 software. The patterns of these findings has resulted in the model for work-life balance according to the Islamic perspective. The results are presented as a guide for the career women nowadays, for those in the higher education institutions, government departments and private companies.
Keywords: Model; Fiqh; work-life balance; successful women; public sector